Two Cautions for a Common Morality Debate: Investigating the Argument from Empirical Evidence Through the Comparative Cultural Study Between Western Liberal Individualist Culture and East Asian Neo-Confucian Culture - Lee, Marvin J. H. (IntechOpen, 2012)
None